Policy Recommendations for Enhancing the Green Banking and Sustainable Development - Dien Vy, Phan; Tam, Phan Thanh (Ital Publication, 2025)
This study examines the key factors influencing green banking and sustainable development in Vietnam to provide evidence-based policy recommendations to promote the integration of sustainability within financial institutions. A mixed-method approach combining qualitative and quantitative analyses was adopted. The research process began with focus group discussions with 30 banking experts, followed by in-depth interviews with senior managers to refine measurement scales. Subsequently, a structured survey was conducted among 900 commercial bank managers in the Southeast region, and the collected data (n = 845 valid responses) were analyzed using exploratory factor analysis, confirmatory factor analysis, and structural equation modeling (SEM). The findings reveal seven knowledge-driven factors that significantly affect green banking and sustainable development: the legal framework and supporting policies, awareness and trends in sustainable consumption, financial technology, leadership commitment and corporate culture, pressure from investors and international organizations, climate change and environmental risk management, and public-private partnerships. Among them, the legal framework and supporting policies emerged as the most influential drivers. Green banking practices are also shown to directly contribute to sustainable development by financing environmentally friendly projects and integrating ESG principles. The study’s novelty lies in its knowledge-based economy perspective, demonstrating how policy knowledge, financial technology, and organizational learning interact to enhance sustainability. Practical implications highlight the need for regulatory reform, technology adoption, and cross-sectoral collaboration to accelerate Vietnam’s transition to a green economy.